A Social Work investigation into the causal factors of relationship problems between stepparents and adolescent stepchildren - Prinsloo, Christina Elizabeth (University of Pretoria, 2013)
Dissertation (MA (SW) (Play Therapy))--University of Pretoria, 2006.